TWIST1 activates cancer stem cell marker genes to promote epithelial-mesenchymal transition and tumorigenesis in esophageal squamous cell carcinoma - Sima Ardalan Khales; Sina Mozaffari-Jovin; Dirk Geerts; Mohammad Reza Abbaszadegan (BMC Cancer, 2022)
Abstract Background Esophageal squamous cell carcinoma (ESCC) is one of the deadliest cancers worldwide. Overexpression of EMT master transcription factors can promote differentiated cells to undergo cancer reprogramming processes and acquire a stem cell-like status. Methods The KYSE-30 and YM-1 ESCC cell lines were transduced with retroviruses expressing TWIST1 or GFP and analyzed by quantitative reverse transcription PCR (qRT-PCR), chromatin immunoprecipitation (ChIP), and immunostaining to investigate the correlation between TWIST1 and stemness markers expression. Cells expressing TWIST1 were characterized for mRNA candidates by qRT-PCR and for protein candidates by Flow cytometry and Immunocytochemistry. TWIST1-ESCC cells were also evaluated for apoptosis and drug resistance. Results Here we identify a role for TWIST1 in the establishment of ESCC cancer stem cell (CSC)-like phenotype, facilitating the transformation of non-CSCs to CSCs. We provide evidence that TWIST1 expression correlates with the expression of CSC markers in ESCC cell lines. ChIP assay results demonstrated that TWIST1 regulates CSC markers, including CD44, SALL4, NANOG, MEIS1, GDF3, and SOX2, through binding to the E-box sequences in their promoters. TWIST1 promoted EMT through E-cadherin downregulation and vimentin upregulation. Moreover, TWIST1 expression repressed apoptosis in ESCC cells through upregulation of Bcl-2 and downregulation of the Bax protein, and increased ABCG2 and ABCC4 transporters expression, which may lead to drug resistance. Conclusions These findings support a critical role for TWIST1 in CSC-like generation, EMT progression, and inhibition of apoptosis in ESCC. Thus, TWIST1 represents a therapeutic target for the suppression of esophageal cell transformation to CSCs and ESCC malignancy.